Conflicts of Interest Arising from the Prudent Investor Rule: Ethical Implications for Over-the-Counter Derivative Securities - Clark, John M. (Journal of business ethics, 2003)
The Prudent Investor Rule creates a potential ethical dilemma for investment advisors selling over-the-counter financial products issued by their firms. The "opportunity" to defraud investors using complex, over-the-counter derivative securities designed for client-specific risk management is much higher than for exchange traded securities. This paper emphasizes the ethical responsibility held by trustees and their organizations to eliminate potential conflict of interests through internal control and monitoring. Independent evaluations of the performance of investment advisors and independent appraisals of complex over-the-counter securities are important in reducing the risks of conflicts of interest. Recent lessons learned from the corporate ethics crisis and requirements of the 2002 Sarbanes Oxley Act would suggest that conflict of interest must be eliminated with third party validation of derivative pricing. By performing due diligence and validation, the trustee is able to satisfy the requirements under the Prudent Investor Rule.